Effects of heavy metals on diesel metabolism of psychrotolerant strains of Arthrobacter sp. from Antarctica - Abdulrasheed, Mansur; Ahmad Roslee, Ahmad Fareez; Zakaria, Nur Nadhirah; Zulkharnain, Azham; Lee, Gillian Li Yin; Convey, Peter; Napis, Suhaimi; Ahmad, Siti Aqlima (Triveni Enterprises, 2020)
Aim: This present study aimed at examining the ability of cold-adapted Antarctic bacteria to tolerate and degrade diesel in the presence of different types of heavy metal co-pollutants. Methodology: Arthrobacter sp. strains AQ5-05 and AQ5-06, originally isolated from Antarctic soils, were grown on Bushnell-Haas medium containing 1 ppm of heavy metal ions (As, Ag, Cd, Co, Cu, Cr, Hg, Ni, and Pb) supplemented with 3% (v/v) diesel. Diesel degradation was determined gravimetrically, while bacterial growth was evaluated by measuring the optical density of media (OD600 nm). Results: In the absence of heavy metal ions, strain AQ5-06 achieved 37.5% diesel mineralisation, while strain AQ5-05 achieved 34.5%. The diesel degrading abilities of both strains were significantly inhibited by exposure to < 1 ppm of Ag or Hg. In contrast, no change in degradation ability was observed using other tested heavy metals. The IC50 of Ag and Hg on diesel degradation by the two strains were (0.2 and 0.4 ppm) and (0.3 and 0.2 ppm), respectively. Interpretation: Arthrobacter sp. Strains AQ5-05 and AQ5-06 may contain genes for alkane degradation and heavy metal resistance for remediating diesel-polluted soil in Antarctic and other cold regions.